Where does the carbon go? A model-data intercomparison of vegetation carbon allocation and turnover processes at two temperate forest free-air CO2 enrichment sites - De Kauwe, Martin G (The New phytologist, 2014)
© 2014 The Authors. New Phytologist © 2014 New Phytologist Trust.